Micro-Sized Enterprises, Innovation and Universities: A Welsh Perspective - Paul Jones (Industry and Higher Education, 2014)
his study considers the linkage between micro-sized enterprises and other organizations, especially universities, in relation to the innovation process. The focus of the research is on non-start-up enterprises in Wales and how they develop their products. The research methodology adopted is a thematic literature review and the case study approach. The findings demonstrate that there are additional barriers to innovation in terms of legislation and regulation when micro-sized enterprises endeavour to overcome their knowledge gap through collaborating with universities. It is noted that there has been minimal research examining the knowledge gap encountered by micro-sized enterprises and how they attempt to overcome the barriers to collaborating with universities.